Dirt - Orenstein, Denise Gosliner, 1950- (New York, NY : Scholastic Press, 2017)
Eleven-year-old Yonder stopped talking when her mother died, and she stopped going to school because of the bullies, knowing that her father would never even notice (although the social worker did); indeed the only creature that seems to care about her is the one-eyed Shetland pony called Dirt who lives on the neighboring farm--so when she discovers that Dirt is about to be sold for horsemeat she is determined to find a way to save him.
Keywords: Human-Animal Relationships -- Juvenile fiction; Human-Animal Relationships -- Fiction; Shetland pony -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Animal welfare -- Juvenile fiction; Fathers and daughters -- Juvenile fiction; Dysfunctional families -- Juvenile fiction; Foster home care -- Juvenile fiction